Efek Dosis–Respons Ekstrak Etanol Daun Cayratia trifolia Linn. pada Edema Kaki Tikus Terinduksi Karagenan - Muzakkir Muzakkir; Bunga Rimta Barus; Meutia Indriana; Salman Salman (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Leaves of Cayratia trifolia Linn. contain several secondary metabolites with potential anti-inflammatory activity. However, evidence regarding the dose–response relationship of their ethanolic extract in acute inflammation remains limited. Objective: To evaluate the anti-inflammatory activity and dose–response trend of Cayratia trifolia leaf ethanolic extract (CTLEE) in a carrageenan-induced rat paw edema model. Methods: Twenty-five male rats (Rattus norvegicus) were divided into five groups (n=5): a 0.5% Na-CMC negative control, a 0.2% diclofenac sodium positive control, and CTLEE treatment groups receiving 100, 200, or 300 mg/kg body weight. Treatments were administered orally, followed 30 min later by an intraplantar injection of 0.1 mL of 1% carrageenan. Paw volume was measured every 60 min for 360 min using a digital plethysmometer. Data were expressed as mean ± SD and analyzed using one-way ANOVA followed by Tukey's post hoc test (p<0.05p<0.05p<0.05). Results: CTLEE reduced paw oedema relative to the negative control and showed a trend toward greater activity as the dose increased. At 360 min, edema percentages were 38.25 ± 11.88%, 29.21 ± 5.36%, and 24.43 ± 6.60% for CTLEE at 100, 200, and 300 mg/kg, respectively, compared with 74.83 ± 13.77% in the negative-control group. The corresponding inhibition values were 48.74 ± 12.10%, 60.24 ± 8.57%, and 65.43 ± 13.96%. Significant differences in paw edema were observed among groups at all assessment times (p<0.001p<0.001p<0.001). Conclusion: CTLEE demonstrated anti-inflammatory activity with a dose-related trend. The 300 mg/kg dose produced the greatest edema reduction and inhibition among the tested extract doses; however, therapeutic equivalence with diclofenac sodium was not established.